Engaging Students with Innovative Teaching Methods through Digital Media at SMK Cut NYADIEN School Semarang - Akhtar, Rana Sharjeel; Santoso, Jarot Tri Bowo (Unram Journal of Community Service, 2025)
This study discovers the efficiency of innovative teaching methods combined with digital media to engage students at SMK Cut Nyadien School Semarang. By leveraging digital tools such as Microsoft applications, YouTube, Google, and Artificial Intelligence (AI), this research estimates how these resources impact student teamwork, innovation, and overall engagements. The study employs a pre-test post-test design with a sample of 28 students. Statistical tests, including normality tests, homogeneity tests, and paired sample t-tests, were shown to evaluate the significance of the interference. The results shows that digital media significantly enhanced student collaboration and innovation scores. Moreover, platforms like YouTube and Google were essential in providing resources for self-directed learning, while AI technologies supported personalized learning experiences. Group studies, study trips, and problem-solving activities additionally contributing to an improved learning environment. These results advocate that digital media and related technologies can significantly improve student engagement and learning results in vocational education